Medical Management of Variceal Bleeding in Patients with Cirrhosis - Juan G Abraldes; Alessandra Dell'Era; Jaime Bosch (Canadian Journal of Gastroenterology)
Bleeding from gastroesophageal varices is a frequent and often deadly complication of cirrhosis. The key factor in the natural history of esophageal varices is increased portal pressure, which in cirrhosis is due to the combination of increased hepatic vascular resistance and increased portal collateral blood flow. The maintenance and aggravation of this situation leads to the progressive dilation of the varices and thinning of the variceal wall, until the tension exerted by the variceal wall exceeds the elastic limit of the vessel, leading to variceal hemorrhage. Mortality from a variceal bleeding episode has decreased in the last two decades from 40% to 20% due to the implementation of effective treatments and improvement in the general medical care. Initial treatment should include adequate fluid resuscitation and transfusion to maintain the hematocrit at 25% to 30%, and prophylactic antibiotics (norfloxacin or amoxicillin-clavulanic acid). It is currently recommended that a vasoactive drug be started at the time of admission. Drug therapy may be started during transferal to hospital by medical or paramedical personnel and maintained for up to five days to prevent early rebleeding. Terlipressin, a vasopressin derivative, is the preferred agent because of its safety profile and proven efficacy in improving survival. Somatostatin is as effective as terlipressin, but may require higher than the usually recommended dosage. Octreotide is effective in conjunction with endoscopic therapy, but is the second choice because it has not been shown to reduce mortality. Vasopressin may be used where terlipressin is not available, but should be given in combination with transdermal nitroglycerin. Endoscopic elastic band ligation is the recommended endoscopic treatment, but injection sclerotherapy is still employed in many centres for active variceal bleeding. Failures of medical therapy (drugs plus endoscopic therapy) should undergo a second course of endoscopic therapy before proceeding to transjugular intrahepatic portosystemic shunt or, in rare occasions, to portosystemic shunt surgery. Administration of recombinant activated factor VII may decrease the number of treatment failures among patients with advanced liver failure (Child-Pugh class B and C).